Territorial organization of the population as an element of state management of spatial development ("Journal "U". Economy. Management. Finance.", 2025)
The article examines spatial development management, population organization and the population's standard of living. These three components are closely related and interdependent, forming the basis for sustainable development of the territory.
Keywords: management of spatial development; population organization; standard of living of the population